Chapter Esperienze di Public History of Education nell'Università di Bologna, tra ricerca scientifica e didattica - D'ASCENZO, MIRELLA (Studi e saggi, 2019)
The contribution explores the Public History of Education activities carried out at the University of Bologna, characterized by the organization of exhibitions and thematic exhibitions as well as research-training actions with schools, aimed at enhancing the historical-educational heritage and collective school memory.